Genomic and transcriptomic profiling of radioresistant prostate and head and neck cancers implicate a BAHD1-dependent modification of DNA damage at the heterochromatin - Chaw Yee Beh; Celestia Pei Xuan Yeo; Boon Hao Hong; Evelyn Mui Cheng Tan; Kah Min Tan; Dennis Jun Jie Poon; Pek Lim Chu; Dewi Susanti; Pei Ling Tai; Monica Ryu; James Proudfoot; Eugenia Li Ling Yeo; et al. (Cell Death and Disease)
Abstract Radiotherapy is an integral modality in treating human cancers, but radioresistance remains a clinical challenge due to the involvement of multiple intrinsic cellular and extrinsic tumour microenvironment factors that govern radiosensitivity. To study the intrinsic factors that are associated with cancer radioresistance, we established 4 radioresistant prostate (22Rv1 and DU145) and head and neck cancer (FaDu and HK1) models by irradiating their wild-type parentals to 90 Gy, mimicking the fractionated radiotherapy schema that is often using in the clinic, and performed whole exome and transcriptome sequencing of the radioresistant and wild-type models. Comparative genomic analyses detected the enrichment of mismatch repair mutational signatures (SBS6, 14, 15, 20) across all the cell lines and several non-synonymous single nucleotide variants involved in pro-survival pathways. Despite significant inter-cell type heterogeneity of their transcriptomic profiles, 18 common dysregulated genes (5 upregulated and 13 downregulated) were identified across the 4 models, including the overexpression of bromo-adjacent homology domain containing 1 (BAHD1) gene, which is involved in heterochromatin formation. Interestingly, this coincided with our observation of increased histone 3 lysine 9 trimethylation (H3K9me3) and histone 3 lysine 27 trimethylation (H3K27me3) expression post-irradiation in our radioresistant cells. The dependency between BAHD1 and heterochromatin formation was confirmed by siRNA knockdown of BAHD1, indicating preferential reduction of H3K9me3 and H3K27me3 expression in the radioresistant cells, but not the wild-type parentals, and confirmed by clonogenic assays showing reversal of radioresistance post-siBAHD1 treatment. We further showed that inhibition of the BAHD1-heterochromatin formation axis led to reduced DNA double-strand break repair. Finally, analyses of treatment outcomes in 4 prostate and head and neck cancer radiotherapy cohorts suggested an increased risk of failures in tumours of high heterochromatin activity. Taken together, our results support a new model implicating BAHD1-dependent modulation of the heterochromatin in acquired radioresistance of prostate and head and neck cancers.